OWE-12 Fungal fumes in faeces – hidden culpritbehindParkinson'sdisease?Afaecal metabolomics study. (June 2019) - Gebeyehu, Gerum Gashaw; Pablo-Fernandez, Eduardo De; Hough, Rachael; Probert, Chris; Emmanuel, Anton; Warner, Tom
Abstract : Introduction: Accumulating evidence implicates the brain gut axis in the pathogenesis of Parkinson's disease (PD). Altered gut permeability may result in afferent vagal transport of an unknown antigen or toxin to the central nervous system, leading to the characteristic dopaminergic neurodegeneration. A study in fruit flies identified the possible role for fungal metabolites, for example 1-octen-3-ol, in a loss of dopamine activity. We investigated the hypothesis that such fungal metabolites might arise from the faeces. We present the results of an evaluation of the faecal metabolome by assessing volatile organic compounds (VOCs) in PD patients. Methods: Using solid phase micro-extraction and gas chromatography and mass spectrometry VOCs were extracted from faecal samples from 35 PD patients (69% male; age 67±8 years; disease duration 11±5 years) and 35 healthy controls (37% male; age 65±8 years). VOCs were identified using automated mass-spectral deconvolution and identification system software and the national institute of standards and technology library. Distinguishing compounds were identified using fold change and t-test and corrected for multiple comparisons; group associations were determined using principal components analysis (PCA) and dendrograms. Findings were compared among groups and correlated with main variables. Results: A mean of 63 VOCs were found from PD samples and 74 from controls (p<0.007). The abundance of VOCs in PD and all controls was compared: 33 differed, 7 of which persisted after correction for multiple comparison, including 2-octanone. PCA showed distinct clustering of groups by disease status (Figure 1). In PD, there was an increased abundance of 2-methyl-6-methylideneoct-2-ene, (6Z)-2, 6-dimethylocta-2, 6-diene and 7-methyl-3-methylideneocta-1, 6-diene and a decreased abundance of cyclohexanecarboxylic acid and methyl pentanoate. Several of the VOCs which increased in PD were fungal metabolites. There was no differences in VOCs in patients compared by disease stage. Conclusions: Metabolomic characterisation in PD patients demonstrates a distinct profile to healthy controls and an increased abundance of fungal metabolites, suggesting a potential role of fungal dysbiosis in PD pathogenesis.